ABO-incompatible living donor kidney transplantation failure due to acute blood group antibody-dependent rejection triggered by human parvovirus B19 infection: a case report and literature review - Dai, Lin-rui; Wang, Xiao-hui; Hou, Yi-bo; Zou, Zhi-yu; Chen, Song; Zhang, Wei-jie; Chang, Sheng (Frontiers in Medicine, 2023)
Background With the improvement of immunosuppressive regimens, the success rate and availability of ABO-incompatible (ABO-i) kidney transplantation (KT) have gradually increased. However, the management of immunosuppression protocols and complications associated with ABO-i KT is complex. Here, we report a clinical case of ABO-i living donor KT with allograft dysfunction caused by acute blood group antibody-dependent rejection triggered by human parvovirus B19 (B19V). Case report The ABO blood group of the recipient was O, and that of the donor was B. The recipient had high baseline anti-B antibody titers (IgM, 1:1024; IgG, 1:64). Before transplantation, he completed a desensitization protocol comprising plasma exchange, double-filtration plasmapheresis, and rituximab, which maintained a low blood group antibody level and resulted in successful transplantation. Two weeks after surgery, the recipient developed a B19V infection combined with acute T-cell-mediated rejection. After the anti-rejection regimen, acute rejection (AR) was successfully reversed, but B19V persisted. One week after AR stabilization, the patient experienced acute antibody-mediated rejection that was more severe and refractory, resulting in the loss of the transplanted kidney. Conclusion Desensitization combined with immunosuppressants can lead to overimmunosuppression and cause various infections. Infections could break the accommodation state of the patient, thereby inducing AR and resulting in the loss of the transplanted kidney.